2014
DOI: 10.1016/j.quascirev.2014.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Timing of deglaciation and postglacial environmental dynamics in NW Iberia: the Sanabria Lake record

Abstract: The multiproxy study (sedimentology, geochemistry and diatoms) of sediment cores from Sanabria Lake (42°07'30'' N, 06°43'00'' W, 1000 m a.s.l.) together with a robust 14 C chronology provides the first high-resolution and continuous sedimentary record in the region, extending back the last 26 ka. The development of a proglacial lake before 26 cal ka BP demonstrates the onset of deglaciation before the global Last Glacial Maximum, similarly to other alpine glaciers in southern European mountains. Rapid deglacia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 134 publications
(237 reference statements)
6
42
0
1
Order By: Relevance
“…7 and 8). These differences in the fre- In terms of humidity, the northwestern IP presented an arid phase that was observed in the marine and lacustrine records (Bernárdez et al, 2008;Jambrina-Enríquez et al, 2014), although towards the east, Enol Lake showed the opposite conditions . In the Pyrenees, Estanya Lake displayed a dry climate scenario (Morellón et al, 2009), whereas the remaining records (Arreo, Montcortès and Basa de la Mora Lakes) displayed large increases in water availability (Corella et al, 2011(Corella et al, , 2013Pérez-Sanz et al, 2013).…”
Section: Roman Period (~250 Bc -500 Ad)mentioning
confidence: 70%
See 1 more Smart Citation
“…7 and 8). These differences in the fre- In terms of humidity, the northwestern IP presented an arid phase that was observed in the marine and lacustrine records (Bernárdez et al, 2008;Jambrina-Enríquez et al, 2014), although towards the east, Enol Lake showed the opposite conditions . In the Pyrenees, Estanya Lake displayed a dry climate scenario (Morellón et al, 2009), whereas the remaining records (Arreo, Montcortès and Basa de la Mora Lakes) displayed large increases in water availability (Corella et al, 2011(Corella et al, , 2013Pérez-Sanz et al, 2013).…”
Section: Roman Period (~250 Bc -500 Ad)mentioning
confidence: 70%
“…General humid and cold conditions were registered by the marine and lacustrine records in the NW IP (Álvarez et al, 2005;Desprat et al, 2003;Jambrina-Enríquez et al, 2014). However, spatial heterogeneity was also observed as indicated by the predominantly warm temperatures of the Penido Vello peat bog (Martínez-Cortizas et al, 1999) and speleothem records from the Cobre, Mayior and Kaite caves (Martín-Chivelet et al, 2011) ( Fig.…”
Section: Early Middle Ages (500 -900 Ad)mentioning
confidence: 86%
“…Several studies suggest that the western Mediterranean region, located at critical geographic and atmospheric boundaries, has experienced abrupt climatic shifts over the Holocene (Anderson et al, 2011;Baldini, 2007;Carri on, 2002;Dorado Valiño et al, 2002;Fletcher et al, 2013;García-Alix et al, 2012;Jalut et al, 2009;Jambrina-Enríquez et al, 2014;Jim enez-Moreno and Anderson, 2012;Moreno et al, 2011;P erez-Obiol et al, 2011;Roberts et al, 2011). Jalut et al (2009) examined circumMediterranean pollen data to derive three climatic phases for the Holocene: i) the early Holocene (11.5e7 ka BP) characterised by increased rainfall, ii) the mid-Holocene (7e5.5 ka BP), characterised by increased variability, linked to decreasing Northern Hemisphere insolation, and iii) the late Holocene, characterised by the onset of a drying trend at~5.5 ka BP.…”
Section: Holocene Climate Variability In the Mediterranean Regionmentioning
confidence: 99%
“…Existing Iberian pollen and lake sediment records (Fig. 1) reveal considerable variability in the timing and character of these phases, thereby impeding our understanding of Holocene climate in the region (Anderson et al, 2011;Carri on et al, 2010;Dorado Valiño et al, 2002;García-Alix et al, 2012;Jalut et al, 2009;Jambrina-Enríquez et al, 2014;Jim enez-Moreno and Anderson, 2012;Moreno et al, 2011;P erez-Obiol et al, 2011;Roberts et al, 2011). Thus, the spatiotemporal pattern of Mediterranean climate advancement within the Iberian Peninsula has remained difficult to constrain.…”
Section: Holocene Climate Variability In the Mediterranean Regionmentioning
confidence: 99%
“…De hecho, Cowton et al (2009) señalaron la ocurrencia de una fase de glaciares de circo, a la que corresponde un conjunto de morrenas que muy probablemente se formaron durante el Dryas Reciente. En los sedimentos del Lago de Sanabria el depósito de una capa detrítica se interpreta asociada a una posible fase de reactivación glaciar entre alrededor de 13,0-12,4 ka BP (Jambrina-Enríquez et al, 2014). Edades de exposición cosmogénica (21Ne) obtenidas en la Sierra de Queixa (Galicia) informan acerca de la ocurrencia de actividad glaciar anterior a 15.4 ± 6.9 ka (Vidal Romaní et al, 1999).…”
Section: Cordillera Cantábrica Y Montañas Del Noroesteunclassified